2021
DOI: 10.3390/foods10010167
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Anti-Inflammatory and Antioxidant Effects of Broccoli Treated with High Hydrostatic Pressure in Cell Models

Abstract: Isothiocyanates (ITCs) are important functional components of cruciferous vegetables. The principal isothiocyanate molecule in broccoli is sulforaphane (SFN), followed by erucin (ERN). They are sensitive to changes in temperature, especially high temperature environments where they are prone to degradation. The present study investigates the effects of high hydrostatic pressure on isothiocyanate content, myrosinase activity, and other functional components of broccoli, and evaluates its anti-inflammatory and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…The extraction process of the bioactive compounds of broccoli was conducted by means of the method proposed by Ke et al [ 63 ]. Fresh and dried broccoli samples were thoroughly dissolved in 80% aqueous methanol at a 1:5 and 1:10 w / v ratio, respectively, and agitated in an orbital shaker (OS-20, Boeco, Hamburg, Germany) at 250 rpm for 1 h, followed by centrifugation at 4193× g for 20 min at 4 °C (5804 R, Eppendorf, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The extraction process of the bioactive compounds of broccoli was conducted by means of the method proposed by Ke et al [ 63 ]. Fresh and dried broccoli samples were thoroughly dissolved in 80% aqueous methanol at a 1:5 and 1:10 w / v ratio, respectively, and agitated in an orbital shaker (OS-20, Boeco, Hamburg, Germany) at 250 rpm for 1 h, followed by centrifugation at 4193× g for 20 min at 4 °C (5804 R, Eppendorf, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Applications of HPP in foods include the inactivation of microorganisms and enzymes and the increase in the shelf life of the products. Furthermore, the use of chemical preservatives is reduced [110]. After HPP on broccoli sprouts with 600 MPa, 85% of GLS were converted to ITCs [111] which suggested the inactivation of the ESP protein.…”
Section: Non-conventional Extractionmentioning
confidence: 99%
“…Moreover, the glucosinolate-myrosinase system in broccoli sprouts was not negatively affected. Two studies [110,112] have reported that the application of HHP at 400 MPa in red cabbage and broccoli generated the highest amounts of ITCs. Moreover, it was found that the activity of myrosinase increased after processing, indicating that the increase in ITCs content is related to the stimulation of myrosinase activity [110].…”
Section: Non-conventional Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a research team conducted an attractive study on high-hydrostatic-pressure technology. They investigated the antioxidant and anti-inflammatory effects of broccoli treated with high hydrostatic pressure in cell models, and reported that this emerging nonthermal technology can enhance the isothiocyanate content of broccoli with antioxidant anti-inflammatory effects, providing an innovative strategy with which to develop healthy food products in the future [ 9 ]. Moreover, an insightful manuscript reported a significant improvement in the antioxidant capacity of puffed turmeric by the application of high hydrostatic pressure extraction.…”
mentioning
confidence: 99%